Emotional Engineering Volume 4 - Fukuda, Shuichi (Springer International Publishing : Imprint: Springer, 2016)
This book describes the important role of emotion in a hyper-connected society and how product development and manufacture change. It explores how our work and lifestyle may be affected by forthcoming technologies and presents key research on multisensory informatics, one of the most important tools for making the most of emotion. This fourth volume of the Emotional Engineering Series focuses on the human issues relating to Cyber Physical Systems, or Industrie 4.0, and discusses the important role emotion plays in these smart environments. Introducing related works in the field of multisensory research, which provide the basic tools for becoming context- and situation aware in this imminent revolutionary society, it discusses not only the changes in production and product development this new revolution will bring about, but also highlights how emotion plays a crucial role in making us happy in such a connected society and in bringing about harmonization between human and human, between human and machine and, last but not least, in maintaining a good work-life balance.